8x+9=12x-5

Simple and best practice solution for 8x+9=12x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+9=12x-5 equation:


Simplifying
8x + 9 = 12x + -5

Reorder the terms:
9 + 8x = 12x + -5

Reorder the terms:
9 + 8x = -5 + 12x

Solving
9 + 8x = -5 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
9 + 8x + -12x = -5 + 12x + -12x

Combine like terms: 8x + -12x = -4x
9 + -4x = -5 + 12x + -12x

Combine like terms: 12x + -12x = 0
9 + -4x = -5 + 0
9 + -4x = -5

Add '-9' to each side of the equation.
9 + -9 + -4x = -5 + -9

Combine like terms: 9 + -9 = 0
0 + -4x = -5 + -9
-4x = -5 + -9

Combine like terms: -5 + -9 = -14
-4x = -14

Divide each side by '-4'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 6v+14=8v+24 | | 12-1/3= | | -2x+1-(-3x+3)=-4+(x-2) | | 12r=18(r+.5) | | -5x+2=10-8x | | r=6(r+.5) | | .3333x+5=.16666(2x-5) | | 12x-3y-10= | | Inx-in(x+3)=6 | | Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= | | r=3(r+.5) | | 11/3×4/9 | | 6-9-(-6)= | | x-2y+74=0 | | 4/9×n=11/3 | | .8=.2+x-0.15 | | 3/100=n/660 | | x+5(x-5)=11 | | 3g+2g+5=0 | | Q^2+16q-15=0 |

Equations solver categories